A tension-induced mechanotransduction pathway promotes epithelial morphogenesis - Zhang, Huimin; Landmann, Frédéric; Zahreddine, Hala; Rodriguez, David; Koch, Marc; Labouesse, Michel (Nature (London), 2011)
Pulled into shape The development and function of many organs depend not only on biochemical signals, but also on the ability of cells and tissues to respond biochemically to mechanical forces — mechanotransduction. Here, Michel Labouesse and colleagues describe a mechanotransduction pathway that links the body wall with the epidermis in the roundworm Caenorhabditis elegans . The pathway involves the p21-activated kinase PAK-1, an adaptor GIT-1 and its partner PIX-1. Tension exerted by muscles or external pressure keeps GIT-1 on station at hemidesmosomes — the small rivet-like bodies that attach epidermal cells to the underlying musculature — and stimulates PAK-1 through PIX-1 and Rac GTPase. The C. elegans hemidesmosome is therefore more than a passive attachment structure — it is a sensor that responds to tension by triggering signalling processes. This study describes a mechanotransduction pathway that links the body wall with the epidermis in Caenorhabditis elegans . The pathway involves the p21 activated kinase PAK 1, an adaptor GIT 1 and its partner PIX 1. Tension exerted by muscles or external pressure keeps GIT 1 on station at hemidesmosomes — the small rivet like bodies that attach epidermal cells to the underlying musculature — and stimulates PAK 1 through PIX 1 and Rac GTPase. The C. elegans hemidesmosome is more than a passive attachment structure, therefore, but a sensor that responds to tension by triggering signalling processes. Mechanotransduction refers to the transformation of physical forces into chemical signals. It generally involves stretch-sensitive channels or conformational change of cytoskeleton-associated proteins 1 . Mechanotransduction is crucial for the physiology of several organs and for cell migration 2 , 3 . The extent to which mechanical inputs contribute to development, and how they do this, remains poorly defined. Here we show that a mechanotransduction pathway operates between the body-wall muscles of Caenorhabditis elegans and the epidermis. This pathway involves, in addition to a Rac GTPase, three signalling proteins found at the hemidesmosome: p21-activated kinase (PAK-1), the adaptor GIT-1 and its partner PIX-1. The phosphorylation of intermediate filaments is one output of this pathway. Tension exerted by adjacent muscles or externally exerted mechanical pressure maintains GIT-1 at hemidesmosomes and stimulates PAK-1 activity through PIX-1 and Rac. This pathway promotes the maturation of a hemidesmosome into a junction that can resist mechanical stress and contributes to coordinating the morphogenesis of epidermal and muscle tissues. Our findings suggest that the C. elegans hemidesmosome is not only an attachment structure, but also a mechanosensor that responds to tension by triggering signalling processes. We suggest that similar pathways could promote epithelial morphogenesis or wound healing in other organisms in which epithelial cells adhere to tension-generating contractile cells.